Quality of match for statistical matches used in the 1995 and 2005 LIMEW estimates for Great Britain - Thomas Masterson (Levy Economics Institute of Bard College, 2011)
The quality of match of four statistical matches used in the LIMEW estimates for Great Britain for 1995 and 2005 is described. The first match combines the fifth (1995) wave of the British Household Panel Survey (BHPS) with the 1995-96 Family Resources Survey (FRS). The second match combines the 1995 time-use module of the Office of Population Censuses and Surveys Omnibus Survey with the 1995-96 FRS. The third match combines the 15th wave (2005) of the BHPS with the 2005 FRS. The fourth match combines the 2000 United Kingdom Time Use Survey with the 2005 FRS. In each case, the alignment of the two datasets is examined, after which various aspects of the match quality are described. In each case, the matches are of high quality, given the nature of the source datasets.
Keywords: C14; C40; D31; 330; statistical matching; wealth distribution; time use; household production; United Kingdom; LIMEW